Moscow invader under the care of the Moscow Church - Kolodnyj, Anatolij Mykolajovyč 1937- (2014)
Muscovites sing: "Everything that I have been traversed is all around me." In this way, they reveal the organic nature of their expansionist nature. This song is in line with the concept of the "Russian world", defended by the Moscow Patriarch Cyril. His "peace" should include all so-called "historical Russia".
Москвини співають: «Все, что мною пройдено, все вокруг мое». В такий спосіб вони виявляють органічно притаманну їм експансіоністську природу. Ця пісня співзвучна і з обстоюваною Московським Патріархом Кирилом концепція «русского мира». До його «мира» має входити вся так звана «историческая Русь».